Risk Factors of Covid-19 Transmission among Health Workers in Southeast Asia - Prathiwi, Qonitah Fitri; Rejeki, Dwi Sarwani Sri; Wijayanti, Siwi Pratama Mars (GLOBAL HEALTH SCIENCE GROUP, 2024)
The transmission of Covid-19 to health workers is an important issue in the pandemic era. Health workers are the front line in handling Covid-19 so they are very vulnerable to being exposed to and even contracting Covid-19 disease. It is necessary to conduct an assessment of the factors that influence the transmission of Covid-19 to health workers, especially in the Southeast Asian Region. The aim of the systematic review is to examine the factors that influence the transmission of Covid-19 cases to health workers in Southeast Asia. The research journal database was retrieved by accessing PubMed and Google Scholar, and using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method using the keywords “risk factors” AND “transmission” AND “Covid-19” AND “health workers”. After going through a series of selections, 11 research journals of 241 journals found that were published in 2020-2023 and were considered relevant for study. Based on the results and discussion of the systematic review, it is known that the factors that influence the transmission of Covid-19 to health workers in Southeast Asia are: average age, type of profession, comorbid history, travel history, community contact at work, contact with Covid-19 patients, adherence to the use of PPE and implementing health protocols, levels of workload, levels of stress and immunization status of health workers.